Power system operation Ed 3 - Robert H Miller; Malinowski, James H (Chennai Mc Graw Hill Education, 2017)
The best-selling power system operation manual ever published--NOW IN AN ALL-NEW EDITION! For over 30 years more electrical power professionals have used this guide for safe, economical system operation than any other in print. Why? Because Power System Operation, by Robert Miller and James Malinowski, presents more of the fundamental principles and methods dispatchers and operators need in a clear, easy-to-understand style. Now this third edition has been expanded by 50% to cover even more: VAR flows; Power system control; Telemetering methods; Supervisory control and data acquisition methods; System control, protection and stability; System reliability factors, Power system energy transfer; Energy accounting in interconnected operations; Operating systems most economically; EHV operation; Power system communications; Impedance of parallel circuits; Effects of resistance on impedance.
Keywords: Electronic Power Systems Management; Load dispatching